2010
DOI: 10.2220/biomedres.31.301
|View full text |Cite
|
Sign up to set email alerts
|

Different distribution of Cav3.2 and Cav3.1 transcripts encoding T-type Ca2+ channels in the embryonic heart of mice

Abstract: We investigated the distribution of T-type Ca 2+ channel mRNAs in the mouse embryonic heart. Cav3.2, but not Cav3.1, was expressed in the E8.5 embryonic heart along with cardiac progenitor markers (Nkx2.5, Tbx5, Isl-1) and contractile proteins (alpha and beta MHC). In the E10.5 heart, the distribution of Cav3.1 mRNA was confirmed in the AV-canal and overlapped with that of MinK or Tbx2. Cav3.2 mRNA was observed not only in the AV-canal but also in the outflow tract, along with MinK and Isl-1, indicating the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The negative chronotropic effect of Ca v 3.1 siRNA and mibefradil is the result of dysfunction of the T‐type Ca 2+ current (Mangoni et al ., 2006). Some investigators have reported that dysfunction of Ca v 3.1 channels during cardiac development affected the development of the cardiac conduction system (Mizuta et al ., 2010). Thus, the decrease in the number of beating aggregates by Ca v 3.1 siRNA may be caused by the dysfunction of conduction system generation in each aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…The negative chronotropic effect of Ca v 3.1 siRNA and mibefradil is the result of dysfunction of the T‐type Ca 2+ current (Mangoni et al ., 2006). Some investigators have reported that dysfunction of Ca v 3.1 channels during cardiac development affected the development of the cardiac conduction system (Mizuta et al ., 2010). Thus, the decrease in the number of beating aggregates by Ca v 3.1 siRNA may be caused by the dysfunction of conduction system generation in each aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the T-type calcium channel (CaV3.2), which is high in early CD166 + cells, decreased significantly at later stages; nevertheless, this decrease was accompanied by a slight increase of the CaV3.1 isoform, the other T-type calcium isoform expressed in the SAN; 24,25 a similar isoform switch between CaV3.2 and CaV3.1 has been previously documented during both mouse development and mouse ESC differentiation. 26,27 Connexin 45, an isoform found in all cardiac regions of the embryonic heart and downregulated after birth, 24,28 was expressed at similar levels in all groups except in early CD166 + cells, where its expression was significantly higher. Finally, in CD166 + cells, we quantified the expression of typical ventricular genes, such as Nkx2.5, Kv4.2, HCN2, and Cx43, and again we found levels similar to those of the SAN rather than those of the ventricle (Figure 4).…”
Section: Cd166 + Cells Express Typical San Genesmentioning
confidence: 94%
“…The cycling conditions included in a hot start at 95°C for 30 s, followed by 45 cycles at 95°C for 5 s, and 60°C for 10 s. To detect LTCC, TTCC and glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) mRNA expression, the gene‐specific primers for these genes were used. Sense and antisense primers (10 n m ) were forward (F) 5′‐TCTGCCTCTCTAGGTCGAA‐3′ and reverse (R) 5′‐GGGAATGTGGTAGGAGAATG‐3′ for LTCC(α1C) (38), forward (F) 5′‐TGTGGAAATGGTGGTGAAGA‐3′ and reverse (R) 5′‐ACTGCGGAGAAGCTGACATT‐3′ for TTCC(α1G) (38), forward (F) 5′‐TGTGTCCGTCGTGGATCTGA‐3′ and reverse (R) 5′‐TTGCTGTTGAAGTCGCAGGAG‐3′ for GAPDH (39). The fluorescent amplification curve of the product was determined, and the cycle at which the fluorescence reached a threshold was recorded ( C t ) in triplicate and averaged.…”
Section: Methodsmentioning
confidence: 99%